Chronic pulmonary aspergillosis in a patient with hyper‐IgE syndrome. Issue 1 (1st December 2021) - Kasuga, Keisuke; Nakamoto, Keitaro; Doi, Kazuyuki; Kurokawa, Nozomi; Saraya, Takeshi; Ishii, Haruyuki
Abstract: Hyperimmunoglobulin E (IgE) syndrome (HIES) is a rare disease with an unclear prognosis. We report a case of HIES comorbid with chronic pulmonary aspergillosis (CPA). A 19‐year‐old male was referred to our department with a medical history of bacterial pneumonia and skin infection. Laboratory data showed an elevated eosinophil count and serum IgE level. Chest computed tomography (CT) showed a pneumatocele and bronchiectasis. On the basis of the clinical and laboratory findings and genetic mutation analysis, we diagnosed him as having HIES. Fourteen months later, he complained of blood‐tinged sputum and haemoptysis. Chest CT showed pneumatocele wall thickening, fungus ball and consolidation. Serum Aspergillus precipitating antibody and serum galactomannan Aspergillus antigen were positive, and Aspergillus fumigatus was detected in the sputum. We diagnosed CPA and treated him using antifungal agents and bronchial artery embolization. CPA is a complication that requires attention in patients with HIES. Abstract : Hyperimmunoglobulin E (IgE) syndrome (HIES) is rare disease characterized by recurrent infections, eczema and increased serum level of IgE. Chronic pulmonary aspergillosis (CPA) is a chronic progressive infectious disease common in patients with underlying pulmonary diseases, but there are few reports of complications due to HIES. We report a case of HIES comorbid with CPA in a teenage male.